The Ramadan Punggahan Tradition in North Sumatra: Investigating the Javanese Nuanced Practicalities in Langkat Regency - Ali, M. Nasihudin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
Javanese people still observe the Punggahan ritual before the month of Ramadan, particularly those who live in Sekoci Village, Besitang District, Langkat Regency, Northern Sumatra Province. The purpose of this study is to ascertain the origins of this practice, how it has evolved, and what the Punggahan tradition means to the Javanese residing in Sekoci Village, Besitang District. A qualitative research methodology is employed in this study. Qualitative data was gathered via library research and interviews. The Javanese community in Sekoci village, Besitang District, is undergoing changes in the way their Punggahan ritual is being carried out. When a group gathers in a mosque or prayer room, the menu is different. This results from the integration of Javanese and Malay culture. This integration resulted in the creation of a specific cuisine that is required at every Punggahan ritual celebration in Sekoci Village, Besitang District. Meat is typically offered on the menu. The tradition of embracing Ramadan in Sekoci Village, Besitang District, originated from this blending of Javanese and Malay customs. The research explores how local communities negotiate the cultural identities that have been transported with them from their home environments to new ones, whereupon they come together to create a new cultural construction. This study serves as a case study of cultural integration and evolution. It demonstrates the importance of adapting traditional practices to contemporary contexts while maintaining their essential cultural significance.